P578 Therapy refractory ulcerative colitis patients may benefit from appendectomy: long-term clinical results from a multicentre prospective cohort series. (16th January 2018) - Stellingwerf, M E; Sahami, S; Winter, D C; Mulcahy, H E; Doherty, G; Cullen, G; Martin, S; D'Haens, G R; Bemelman, W A; Buskens, C J
Abstract: Background: Appendectomy may lead to a reduction in relapses and need for medication in patients with ulcerative colitis (UC). However, the possibility of a placebo effect is still debated, as long-term prospective data are lacking. The aim of this study was to analyse the effect of an appendectomy on the clinical course of therapy refractory UC patients. Methods: In this observational prospective cohort study, a consecutive series of refractory UC patients referred for proctocolectomy between November 2012 and June 2015 were counselled to undergo laparoscopic appendectomy first. Primary endpoint was clinical response at 12 months and long-term follow-up (>2 years), defined as a decrease of ≥3 points in the partial Mayo ranging from 0 to 9. Secondary endpoints were failure (colectomy or start of new, mostly experimental medication), endoscopic remission (endoscopic Mayo score ≤1), changes in IBDQ (range 32–224), and a patient rated 'global change' question ("Since your operation, have your UC symptoms improved overall?"). The minimal clinically important difference (MID) in IBDQ was calculated from the difference in IBDQ change scores of the patients answering "yes" and "no" to the global change question. Statistical differences were analysed using mixed-models analysis for repeated measures applying a random-effects model. Results: In total, 28 patients (46% female, 10 using steroids) with a median age of 41 (IQR, 33–48) underwent appendectomy with a median pre-operative partial Mayo score of 7 (IQR, 6–8). The mean baseline IBDQ was 127 (95% CI 113–141). After 12 months, 12 of 26 (46%) patients had a clinical response, none using steroids. Of those with a response, 3 of 12 refused endoscopy and 5 of 12 were in endoscopic remission. A total of 10 patients failed (6x colectomy, 4× experimental medication). For the remaining patients, the IBDQ significantly improved to mean 161 (95% CI 144–177; p < 0.001). Long-term data were available for 27 of 28 patients. After median follow-up of 4 years (range 2–5) another three patients failed (in total 9× colectomy, 4× experimental medication). Thirteen of the remaining 14 patients had clinical response (4 using steroids) of whom 6 were in endoscopic remission (endoscopy data of three patients is pending). The IBDQ was further improved to mean 169 (95% CI 151–188; p < 0.001). Overall, 77% of the patients answered "yes" to the global change question, the MID for improvement of the IBDQ was 26 points resulting in a clinical benefit for 75% of the patients. Conclusions: After long-term follow-up, appendectomy resulted in a clinical response in at least 48% of refractory UC patients of whom 46% were in endoscopic remission. An appendectomy could be beneficial in this patient group, as a long-term (endoscopic) placebo effect seems unlikely.